Pengembangan Digital Marketing untuk UMKM Kreatif dan Inovatif di Desa Sampiran Kecamatan Talun Kabupaten Cirebon - Ade Johar Maturidi; Yunita Indah Lestari; Dina Fatimah Azzahra (LPPM POLITEKNIK LP3I, 2024)
Digital Marketing refers to a series of online marketing and product sales techniques used to advertise goods and services through various digital platforms. This requires the use of technology, digital channels and social media as a platform to reach audiences or targets, build brand awareness or brand image, and generate significant sales. Digital marketing development is very important, especially for UMKM players, Micro, Small and Medium Enterprises (UMKM) are Micro, Small and Medium Enterprises (UMKM) which are one of the business sectors that have a large role in a country's economy. They usually consist of smaller companies with fewer employees and a more limited operational scope. Therefore, it is very necessary to develop digital marketing for UMKM players to be more creative and innovative, considering that we are currently in a position of adjustment after the Covid-19 pandemic. Many UMKM experienced a decline in sales and were unable to develop and even went bankrupt. This condition makes UMKM players have to think about how to survive for the sake of their business continuity. It is known that many UMKM players have not followed digital developments to the fullest, especially due to a lack of knowledge about digital marketing. The aim of the digital marketing development workshop for UMKM in Sampiran Village, Talun District, Cirebon Regency is to provide digital marketing training assistance as an effort to develop and expand technology-based (digital) marketing networks. After carrying out this service, it is hoped that UMKM actors in the area will continue to work together for the sustainability of UMKM and community economic development.